Can We Hit Two Birds with One Stone: An Effectiveness Study of Peer-support Groups for Low-income Spousal and Adult Children Caregivers of Hong Kong Older Adults. Issue 3 (2nd April 2020) - Zhou, De-Hui Ruth; Hung, Suet-Lin; Lo, Temmy Lee Ting
ABSTRACT: This study aims to assess the effectiveness of peer support groups for low-income older adults' caregivers in the Hong Kong community. It compares the effectiveness of peer support groups on spouse and adult children caregivers. The peer support program was structured into three stages, including six training sessions for peer specialists, eight caregiver support group sessions, and non-structured informal contact. The study adopted a quasi-experiment design supplemented with qualitative data collected from focused group interviews. It involved a user group of 58 participants and a control group of 42 participants. Both quantitative and qualitative data were collected before, after the peer support groups, and at a three-month follow-up. The quantitative results showed that the peer support program was more effective in promoting social support for adult children caregivers but not for spousal caregivers. Three focus group interviews suggested that the community-based peer-support group could be helpful to improve stress management, emotional regulation skills, and social networks of the caregivers. Based on the research findings, we discuss the various needs of spousal and adult children caregivers, provide recommendations for service providers and practitioners to consider homogenous group services to address the diverse needs of spousal and adult children caregivers.